2010
DOI: 10.1089/aid.2010.0021
|View full text |Cite
|
Sign up to set email alerts
|

The Relatedness of HIV Epidemics in the United States–Mexico Border Region

Abstract: Phylogeography can improve the understanding of local and worldwide HIV epidemics, including the migration of subepidemics across national borders. We analyzed HIV-1 sequences sampled from Mexico and San Diego, California to determine the relatedness of these epidemics. We sampled the HIV epidemics in (1) Mexico by downloading all publicly available HIV-1 pol sequences from antiretroviral-naive individuals in GenBank (n = 100) and generating similar sequences from cohorts of injection drug users and female sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Similar to our previous reports ( Mehta et al, 2010 ), we found significant compartmentalization between the sampled HIV epidemics in San Diego and Tijuana (Fst p < 0.001). Nevertheless, of the 14 clusters that included individuals from Tijuana, five of these clusters included individuals who lived in San Diego.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our previous reports ( Mehta et al, 2010 ), we found significant compartmentalization between the sampled HIV epidemics in San Diego and Tijuana (Fst p < 0.001). Nevertheless, of the 14 clusters that included individuals from Tijuana, five of these clusters included individuals who lived in San Diego.…”
Section: Resultssupporting
confidence: 91%
“…Along international borders, like the San Diego–Tijuana region, understanding the dynamics of HIV transmission across reported risks, racial/ethnic groups, and geography on each side of the border, and how the epidemics are linked, will be important in the implementation of effective prevention efforts ( Mehta et al, 2010 ). Since HIV evolves rapidly, viral sequences isolated from infected individuals are typically unique, and transmission networks can be inferred by identifying sequences that are genetically closely related ( Smith et al, 2009 , Wertheim et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect introductions from other geographical areas such as North America and South America, perhaps associated with emigrants returning to their countries. Reported evidence of the link between the HIV-1B epidemics in the US and Mexico [60][62], or between epidemics in Panama and South America [8], would be compatible with this idea. Importantly, considering the relative long period of asymptomatic infection of HIV-1B, we should expect that the first AIDS reports must occurred around 8–10 years later of the true TMRCAs.…”
Section: Discussionmentioning
confidence: 88%
“…7,39,40,[45][46][47][48][49][50] Only patients in care were recruited into the study; individuals who abandoned treatment entirely due to mobility were not included in the sample. Another limitation is that this study does not provide data on the extent of mobility in the overall population of Dominicans living with HIV.…”
Section: Discussionmentioning
confidence: 99%